New localities of the Oryzias woworae species group (Adrianichthyidae) - Kazunori Yamahira; Koji Mochida; Shingo Fujimoto; Daniel F. Mokodongan; Javier Montenegro; Takuma Kaito; Asano Ishikawa; Jun Kitano; Taketoshi Sue; Mulis Mulis; Renny K. Hadiaty; Ixchel F. Mandagi; K.W. Alex Maseng (Jurnal Iktiologi Indonesia, 2016)
The Oryzias woworae species group, composed of O. asinua, O. wolasi, and O. woworae, is a group of the family Adrianichthyidae endemic to Sulawesi Tenggara (Southeast Sulawesi). Here, we report new localities of each of the three species in this group, which were collected during our field expeditions in 2014-2015. In total, six new localities were discovered throughout Sulawesi Tenggara, including Muna Island, suggesting that they may have wider species ranges than currently recognized. Some of the new localities were independent of the river systems of the known localities, suggesting that each species is genetically structured, and that the unit for conservation should be considered not as each species but as each local population. Abstrak Kelompok spesies Oryzias woworae, family Adrianichthyidae, terdiri atas O. asinua, O. wolasi, dan O. woworae, merupakan spesies endemik di Sulawesi Tenggara. Selama ekspedisi lapangan tahun 2014-2015, kami mencatat setiap spesies dari ketiga spesies dalam grup ini dijumpai di beberapa lokasi baru. Secara keseluruhan, enam lokasi baru telah ditemukan sepanjang daerah Sulawesi Tenggara, termasuk Pulau Muna, yang menunjukkan bahwa grup tersebut kemungkinan memiliki daerah persebaran lebih luas dari yang diketahui saat ini. Sebagian lokasi baru berasal dari sistem aliran sungai yang berbeda dengan lokasi yang telah diketahui selama ini. Hal ini menunjukkan bahwa tiap spesies terstruktur secara genetik, dan bahwa unit konservasi harus dipertimbangkan bukan untuk tiap spesies tetapi untuk tiap populasi lokal.